The Iraqi -Jordanian relations after 2003" (Tikrit Journal For Political Science, 2016)
Iraqi Jordanian relations has been affected by many subjective circumstances since both of them was the result of the colonial division at the beginning of the twentieth century and both of the countries was under the British control who made the rule in both of them belong to a king from the Hashimet family , but things had changed after that , Iraq had witnessed a revolution that changed the nature of the governance and the political system as a whole but this did not stop the relations between the two countries . Iraq is now living in a critical period that started in 2003 , it is passing in transitional period whether in its internal affairs or in its foreign relations and especially with Jordan as a neighboring country and this is what we are trying to analyze in this research.
Keywords: Political cooperation Economic partnership Land borders Cultural exchange Security coordination